Effects of different fertilization treatments on ground-dwelling arthropods and their functional groups in agricultural landscapes - Bian, Ziqi; Liu, Lyuyi; Li, Yan; Li, Yanli; Ding, Shengyan (Frontiers in Ecology and Evolution, 2025)
Intensive agriculture has caused significant declines in ground-dwelling arthropod diversity and ecosystem services. Chemical and organic fertilizers alter arthropod habitats, affecting arthropod community abundance and diversity. Fertilization treatments differentially affect arthropod communities, and various soil physico-chemical properties differentially affect various species in the arthropod community. Studying arthropod diversity, community structure, and soil physico-chemical properties under various fertilization treatments is crucial to understanding the impact of agricultural activities. We used pitfall traps to catch ground-dwelling arthropods four times a year, and analyzed arthropod abundance and biodiversity indices under different fertilization treatments The study revealed that Lycosidae and Araneidae were the dominant family in the study area. Notably, the application of both chemical and organic fertilizers led to a decrease in ground-dwelling arthropod diversity compared to unfertilized treatments. Furthermore, our analysis indicated that the strongest environmental predictors of ground-dwelling arthropod community variation varied depending on the fertilization method, and different species were affected differently by soil physico-chemical properties. Specifically, when no fertilization was applied, soil total potassium and available phosphorus were the strongest predictors of arthropod diversity. Conversely, organic matter became the primary determinant when organic fertilizers were used alone. Interestingly, when chemical and organic fertilizers were combined, soil total nitrogen, pH, and available phosphorus were identified as the principal drivers. Additionally, our findings highlighted that the dominant group of ground-dwelling arthropods was particularly sensitive to changes in biomass, available nitrogen, and available potassium.